Stereoselective Total Synthesis of the Diastereomeric Tricyclic Alkaloids Tetraponerine-7 and Tetraponerine-8 Using O-Pivaloylated d-Arabinopyranosylamine as the Common Auxiliary - Strassnig, Irina; Körber, Karsten; Hünger, Udo; Kunz, Horst (Synthesis, 2015)
Based on a diastereoselective domino Mannich–Michael reaction cascade of 2-N-[(S)-3-{(benzyloxycarbonyl)[4-(tert-butyldiphenylsiloxy)butyl]amino}octylidene]-2,3,4-tri-O-pivaloyl-α-d-arabinopyranosylamine with the Danishefsky diene, the major component of the neurotoxic venom of the New Guinean ant Tetraponera punctulata, tetraponerine-8, and its diastereomer tetraponerine-7 were synthesized in pure form. While the Mannich reaction of the arabinosyl imine of the required (S)-configured β-aminoaldehyde gave the 2-substituted piperidinone precursor of tetraponerine-8 with excellent diastereoselectivity, the analogous Mannich reaction of the (R)-configured β-aminoaldehyde afforded the precursor of tetraponerine-7 with a selectivity of only 2:1 (mismatched case). The enantiomerically pure tetraponerine-8, described as highly toxic for ants, exhibited only moderate toxicity to sucking and stinging insects.
Keywords: piperidine alkaloids; tetraponerines; stereoselective Mannich–Michael reaction; carbohydrate auxiliaries; nicotinic acetylcholine receptor inhibitor